Impact of Sense of Belonging and Self-Awareness on Professionalism of Teachers (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study was aimed to determine the relationship between self-awareness and sense of belonging on the professionalism of teachers. The research approach used is quantitative correlative involving research subjects as much as 32 teachers. The subjects were chosen by purposive sampling. The instruments used are self-awareness scale, Sense of Belonging Instrument (SOBI), and scale of professionalism. Data analysis using partial correlation test. The results showed that there is a relationship between self-awareness with a significant professionalism with very strong correlation criteria. But there is no significant relationship between sense of belonging with professionalism with very low correlation criteria. Then there is a significant relationship between self-awareness and sense of belonging with professionalism with low correlation criteria. Each relationship has a positive relationship direction. This study provides clarification of the relationship between self-awareness, sense of belonging, and professionalism.